2019
DOI: 10.1002/nau.23958
|View full text |Cite
|
Sign up to set email alerts
|

Stress urinary incontinence after vaginal prolapse repair: development and internal validation of a prediction model with and without the stress test

Abstract: Objective To develop a prediction model for stress urinary incontinence (SUI) after vaginal prolapse repair (postoperative stress urinary incontinence [POSUI]) and assess the value of a preoperative stress test. Patients and methods Secondary analysis of two trials in which women were randomised for prolapse repair with or without a midurethral sling (MUS). The trials included women with (CUPIDO‐1, n = 134) and without (CUPIDO‐2, n = 225) coexisting SUI. POSUI was defined as bothersome SUI one year after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Diabetes mellitus was included in our model as a predictor but not in the CUPIDO model. This discrepancy might arise from differences in the prevalence of diabetes mellitus between the two study’s participants; 18% of patients in our cohort had diabetes mellitus compared with only 5% among CUPIDO participants 7 . Preoperative POPQ point Ba was not included in our model as a predictor.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Diabetes mellitus was included in our model as a predictor but not in the CUPIDO model. This discrepancy might arise from differences in the prevalence of diabetes mellitus between the two study’s participants; 18% of patients in our cohort had diabetes mellitus compared with only 5% among CUPIDO participants 7 . Preoperative POPQ point Ba was not included in our model as a predictor.…”
Section: Discussionmentioning
confidence: 89%
“…This discrepancy might arise from differences in the prevalence of diabetes mellitus between the two study's participants; 18% of patients in our cohort had diabetes mellitus compared with only 5% among CUPIDO participants. 7 Preoperative POPQ point Ba was not included in our model as a predictor. However, stage I anterior vaginal wall prolapse (Ba <−1) was identified as an increased risk in the CUPIDO model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that the incidence of pelvic bladder and uterine prolapse in SUI patients accounted for about 25% [ 15 ]. After surgery, pelvic bladder and uterine prolapse accounted for 15% [ 16 ]. In this study, pelvic floor dynamic MRI images showed that the incidence of pelvic bladder and uterine prolapse in experimental patients with SUI was greatly superior to controls ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%